2016
DOI: 10.1136/bmjopen-2015-010099
|View full text |Cite
|
Sign up to set email alerts
|

Identification of responders to inhaled corticosteroids in a chronic obstructive pulmonary disease population using cluster analysis

Abstract: ObjectivesTo identify clusters of patients who may benefit from treatment with an inhaled corticosteroid (ICS)/long-acting β2 agonist (LABA) versus LABA alone, in terms of exacerbation reduction, and to validate previously identified clusters of patients with chronic obstructive pulmonary disease (COPD) (based on diuretic use and reversibility).DesignPost hoc supervised cluster analysis using a modified recursive partitioning algorithm of two 1-year randomised, controlled trials of fluticasone furoate (FF)/vil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 29 publications
0
37
1
2
Order By: Relevance
“…As the majority of our subjects in this study were treated with systemic corticosteroid and antibiotic therapy, we speculated that subjects with higher blood eosinophil count might have a better response to therapy and thus quicker recovery and shorter LOS. Some studies reported that stable COPD patients with high sputum and blood eosinophil counts had a better response to ICS for preventing exacerbations . However, a study found that the effect of indacaterol–glycopyrronium (long‐acting beta‐agonist (LABA) and long‐acting anti‐muscarinic agent (LAMA)) versus salmeterol–fluticasone (LABA + inhaled steroid) on the reduction of the rate of COPD exacerbations was independent of the baseline blood eosinophil count .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the majority of our subjects in this study were treated with systemic corticosteroid and antibiotic therapy, we speculated that subjects with higher blood eosinophil count might have a better response to therapy and thus quicker recovery and shorter LOS. Some studies reported that stable COPD patients with high sputum and blood eosinophil counts had a better response to ICS for preventing exacerbations . However, a study found that the effect of indacaterol–glycopyrronium (long‐acting beta‐agonist (LABA) and long‐acting anti‐muscarinic agent (LAMA)) versus salmeterol–fluticasone (LABA + inhaled steroid) on the reduction of the rate of COPD exacerbations was independent of the baseline blood eosinophil count .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that stable COPD patients with high sputum and blood eosinophil counts had a better response to ICS for preventing exacerbations. [16][17][18][19] However, a study found that the effect of indacaterolglycopyrronium (long-acting beta-agonist (LABA) and long-acting anti-muscarinic agent (LAMA)) versus salmeterol-fluticasone (LABA + inhaled steroid) on the reduction of the rate of COPD exacerbations was independent of the baseline blood eosinophil count. 20 Less information is available regarding the effect of peripheral eosinophil count on the response of patients during AECOPD.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has proved diffident to define these consistently. Several attempts have been made to distinguish different clinical phenotypes using cluster analysis . However, these clusters are not consistent between different studies and populations and may not be stable so have not proved to be useful in selecting treatment.…”
Section: Copd Phenotypesmentioning
confidence: 99%
“…In a separate post hoc analysis of two large multinational studies comparing treatment with inhaled once daily fluticasone furoate/vilanterol to once daily vilanterol, Hinds et al found that patients with eosinophil count >2.4%, generally, responded better to fluticasone furoate/vilanterol 19. However, there was an additional influence of tobacco smoking on the outcomes.…”
Section: Potential Role Of Blood Eosinophil Count In Predicting a Resmentioning
confidence: 99%